Vulnerabilities in Social Assistance. Volume/2022 - BREAZ, MARIA-ALINA (2023)
Social assistance, as a subsidiary system of social protection, operates by a principle other than insurance: it is based only on state budget funds or donations from volunteers and international institutions and does not involve any previous financial contribution from the assisted person.